2017
DOI: 10.1016/j.jneuroling.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Converging evidence for [coronal] underspecification in English-speaking adults

Abstract: The goal of this study was to test the predictions of the Featurally Underspecified Lexicon (FUL) theory by examining event-related potential (ERP) indices of phonological representation. Two English consonants differing in place of articulation were selected: [labial] /b/ and [coronal] /d/. It was assumed that the phonological representation of /d/ contained less distinctive feature information due to its [coronal] place of articulation, as compared to /b/. English-speaking adults were presented with two syll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 67 publications
(104 reference statements)
4
22
1
Order By: Relevance
“…On the other hand, in the children with PD, the /bA/ mismatch response was significantly more positive than was the mismatch response to /dA/. Both of these findings were contrary to previous to adult [coronal] underspecification findings (Cummings et al, 2017) wherein the underspecified /dA/ elicited a larger MMN than did the specified /bA/.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, in the children with PD, the /bA/ mismatch response was significantly more positive than was the mismatch response to /dA/. Both of these findings were contrary to previous to adult [coronal] underspecification findings (Cummings et al, 2017) wherein the underspecified /dA/ elicited a larger MMN than did the specified /bA/.…”
Section: Discussioncontrasting
confidence: 92%
“…As a result, even though the specified phoneme has a contrasting feature, a no-mismatch occurs when it is the deviant-resulting in a small or no mismatch response. The adults in Cummings et al (2017) followed this response pattern. This proposed developmental model is consistent with previous proposals of children's speech processing (Bernhardt, 1992;Kuhl, 2000).…”
Section: A Developmental Model Of Phonological Underspecificationmentioning
confidence: 65%
See 1 more Smart Citation
“…we therefore propose that the explanations put forth by the proponents of the FUL (Lahiri & Reetz, 2002; fit our findings and the asymmetries in the linguistic MMN literature the best. In this relation, a number of studies have found support for [coronal] as an underspecified place of articulation feature in German for both plosives and vowels (Cornell et al, 2011;Eulitz & Lahiri, 2004;Scharinger et al, 2010;2012a), and in English for plosives and fricatives (Cummings et al, 2017;Schluter et al, 2016), and, as already mentioned, for [voice] as an underspecified laryngeal feature in English (Hestvik & Durvasula, 2016;Phillips et al, 2000). To these findings, our present study adds an investigation of the laryngeal feature…”
Section: Perceptual Asymmetry and The Mmnsupporting
confidence: 79%
“…compare "lea [m] bacon" (instead of "lea[n] bacon") with "la [m]e duck" (and not "la[n]e duck") (examples are from Lahiri & Reetz, 2002;Scharinger, Bendixen, Trujillo-Barreto, & Obleser, 2012a). Using the MMN to probe predictions from the FUL framework, several studies have found asymmetries in the MMN to English, German and Dutch stimuli in support of certain underspecified phonological features (Cornell, Lahiri, & Eulitz, 2011;Cummings, Madden, & Hefta, 2017;Diesch & Luce, 1997;Eulitz & Lahiri, 2004;Hestvik & Durvasula, 2016;Scharinger et al, 2012a;Scharinger, Lahiri, & Eulitz, 2010;Schluter, Politzer-Ahles, & Almeida, 2016;Walter & Hacquard, 2004). However, Scharinger et al (2011) reported nonsupportive findings, Tavabi et al (2009) only found partially supportive effects, and Bonte et al (2005) found evidence of a phonotactic effect rather than of underspecification.…”
Section: Introductionmentioning
confidence: 99%